The Effectiveness of The Team Game Tournament (TGT) Cooperative Learning Model in Increasing Student Activeness in Learning Big Ball Games - Hidayat, Firman; Sonjaya, Azhar Ramadhana; Hermawan, Irwan (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2026)
Student engagement in physical education, particularly in learning large-ball games, remains a critical issue, as many students tend to be passive and less engaged during these activities. This study aims to determine the effectiveness of the TGT (Team Games Tournament) cooperative learning model in improving student engagement in learning large ball games. This study used a quasi-experimental design with a non-equivalent control group design. The sample consisted of 26 students selected through purposive sampling. Data were collected using a student engagement questionnaire and analyzed using descriptive statistics and a one-sample t-test. The results showed that the average student engagement score increased from 91.27 (pretest) to 97.46 (posttest), a 33.11% increase. Statistical analysis showed a significant difference between the pretest and posttest scores, indicating that the TGT model has a significant effect on student engagement. The TGT cooperative learning model is effective in improving student engagement in learning large-ball games and can be considered an alternative strategy to encourage active participation in physical education.